TERROR IN THE CAPITAL - Raharjo, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Again, Jakarta rocked by bomb. Terrorism which did not show up after a long time, now has appeared near the centers of power - Sarinah, M.H. Thamrin Street - within a stone's throw to the State Palace. This event is quite shocking for two reasons. First, it has been a while since the act of terrorism does not appear with the assumption that the religious deradicalization program successfully executed and terrorist acts to focus more on Santoso cs group in Poso. Second, this action occured at a time when the executive, legislative and non-governmental organizations rowdy about the revision of anti-terrorism laws.....